2014
DOI: 10.1016/j.jobcr.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of 3 Mix and Other Mix in non-instrumental endodontic treatment of necrosed primary teeth

Abstract: a b s t r a c tProblem considered: The objective was to evaluate and compare the clinical and radiographic efficacy of two different combinations of antibacterial drugs when used in noninstrumental endodontic treatment of necrosed primary teeth.Materials and method: Forty teeth were randomly divided into two groups, viz. groups A and B having 20 teeth each. In Group A, 3 Mix (ciprofloxacin, metronidazole, and minocycline) and in Group B, Other Mix (ciprofloxacin, ornidazole, and minocycline) mixed with propyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 12 publications
0
39
1
9
Order By: Relevance
“…Cruz et al found that propylene glycol delivered dye through the root canal system rapidly and more effectively indicating its potential use in delivering intracanal medicament. 11 In the study conducted by Takushige et al, 9 Prabhakar et al, 8 Nanda et al, 12 and Pinky et al, 7 medication cavity was prepared prior to the placement of 3Mix in which the orifice were enlarged with straight bur to receive the medicament. However, medication cavity was not prepared in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Cruz et al found that propylene glycol delivered dye through the root canal system rapidly and more effectively indicating its potential use in delivering intracanal medicament. 11 In the study conducted by Takushige et al, 9 Prabhakar et al, 8 Nanda et al, 12 and Pinky et al, 7 medication cavity was prepared prior to the placement of 3Mix in which the orifice were enlarged with straight bur to receive the medicament. However, medication cavity was not prepared in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that when a systemic antibiotic is administered, only a small part of the drug concentration reaches the root canal, which makes it of little benefit. In view of the above, the application of local antibiotics allows to administer substantially higher concentrations and to avoid systemic complications (Nanda et al 2014). This evidence has allowed for several years in the Pediatric Dentistry Specialty Clinic from the Autonomous University of Zacatecas to establish a non-instrumented endodontic treatment in primary teeth by using an antibiotic paste containing the antibacterial drug mixture for the treatment of dental organs with pulp involvement and doubtful prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the above, the application of local antibiotics allows to administer substantially higher concentrations and to avoid systemic complications. 25 This evidence has allowed for several years in the Pediatric Dentistry Specialty Clinic from the Autonomous University of Zacatecas to establish a non-instrumented endodontic treatment in primary teeth by using an antibiotic paste containing the antibacterial drug mixture for the treatment of dental organs with pulp involvement and doubtful prognosis. This biological approach is considered innovative because mechanical instrumentation is not required, which avoids further root canal expansion, unnecessary irritation on periapical tissues, decreasing operative times (performed in a single appointment), and can be applied satisfactorily in young children during early childhood.…”
Section: Discussionmentioning
confidence: 99%